Electrochemical SPM study of 2D phase and 3D phase formation of Zn at the ionic liquid / Au(111) interface [online] - Dogel, Jana (KIT Scientific Publishing, 2004)
Zn electrodeposition in the under- (UPD) and overpotential (OPD) ranges by means of in-situ Scanning Tunneling Microscopy (STM) was examined, supported by in-situ cyclic voltammetry and chronoamperometrie. The underpotential deposition of Zn follows a layer-by-layer growth. For the first time the formation of three successive Zn monolayers has been observed in the UPD range. It has been shown, that the UPD of Zn is complicated due to surface alloying. The same growth mechanism extends from the UPD into OPD range until Al bulk deposition sets in. The UPD of Al at 100 mV vs. Zn/Zn(II) is marked by Moiré pattern formation. For the first time in this system the effective tunneling barrier f has been measured by STS. A first insight into the 2D phase formation of electrodeposited Zn at the electrolyte / electrode interface was obtained from STM images at various times and potentials. Before a coherent layer is formed wormlike structures are observed characteristic of spinodal decomposition. This implies a first order phase transition, which has been resolved here for the first time for 2D electrodeposition.